Silver-catalyzed tandem 5- and 6-endo-cyclizations via concomitant yne-ol-imine activation: selective entry to 2-aryldihydrofuroquinolines. (16th August 2021) - Karmakar, Swastik; Das, Prasanta; Kundu, Sandip
Abstract : Ag(i )-catalyzed domino imination-intramolecular bi-heterocyclization-aromatization cascade has been developed to construct 2-aryldihydrofuroquinolines from aldehyde and unprotected 4-(2-aminophenyl)but-3-yn-1-ol via tandem 5- endo-dig and 6- endo-trig cyclization. Abstract : A silver(i ) catalyzed domino imination-intramolecular biheterocyclization-aromatization cascade has been developed to construct 2-aryl/-heteroaryl dihydrofuroquinolines in moderate to good yield using an aldehyde and unprotected 4-(2-aminophenyl)but-3-yn-1-ol as precursors. Sequential Ag-(i )-induced 5- endo-dig cyclization of the yne-ol part and 6- endo-trig cyclization of a proposed Ag-bound imine, followed by aromatization, furnish the furoquinoline derivatives.